(untitled) (Revista Internacional de Folkcomunicação, 2019)
We propose, in this essayistic bibliographical research, to put into dialogue two different attempts to explain the world: the notion of paradigm, according to Kuhn, and the mythological functions, according to Campbell. The intention is to show that the different lenses we use to see the world make up different worlds. Thus, we seek to show two communication perspectives: the sign’s economy of Pross and the communication’s ecology of Romano. We consider, with our reflections tributary to the complexity of Morin, the role of the Imaginary (from Morin) and Communication, in the sharing - Kuhn points out as necessary characteristic for the institution of both a paradigm and a community - of a change of perspective. Communication; Imaginary; Epistemology; Complexity; Communication’s Ecology.